Developing the high energy performance standards for oil-injected air-cooled screw air compressor for Thailand - Kengkamon Wiratkasem; Somchai Pattana; Korrakot Yaibuathet Tippayawong; Nakorn Tippayawong (Energy Reports, 2020)
The objective of this wok was to develop the high energy performance standards (HEPS) for oil-injected air-cooled screw air compressors in Thailand. Based on the data from the Customs Department in 2018, it was found that Thailand imported a great number of air compressors with total value of more than 60 million USD. In this study, the energy performance of the air compressors was evaluated from standardized tests, and the energy performance data was used to analyze the energy efficiency standards using statistical principles of normal curves and standard scores. The criteria used in determining the HEPS was that about 30% of the products must have the specific power higher than the HEPS value. The HEPS value was shown in the form of equations to be able to use with all the power input. If it is promoted to adopt this HEPS, Thailand will have the potential to save energy by about 37,305,000 kWh/year.
Keywords: 330; Energy efficiency; Air-cooled oil-injected; HEPS; Screw air compressor